Clinical and electrophysiologic analysis of subclinical hypothyroidism in a hospital population - Pérez-Galdós, Proel (2019)
Objective: To investigate the effects of subclinical and clinical primary hypothyroidism on peripheral nerve function. Methods: Prospective study of selected patients diagnosed with subclinical and clinical primary hypothyroidism with sensory or motor symptoms; there were analyzed demographic variables, types of hypothyroidism, treatment with levothyroxine (LT4). The presence of polyneuropathy or focal neuropathy was defined with studies of nerve conduction velocity. Results: We studied 33 patients diagnosed with clinical hypothyroidism (CH) and subclinical (SCH); the average age was 64.76 years; 90.9% of the patients were female. Pain and paresthesia of the extremities were the most frequent symptomatology. In the CH the levels of TSH and free T4 were normal, in the SCH the average levels of TSH and free T4 were in 11.40 mU/L and 0.85 ng/dl respectively. When performing the neurophysiological tests, it was observed that 42.4% of the patients had alterations in the studies of sensory or motor nerve conduction, in general. Conclusions: There is a limited number of functional studies at the level of the Peripheral Nervous System in patients with this disorder. The peripheral nerve involvement in hypothyroidism is probably related to the duration of the disease and influenced by the specific treatment.